2021
DOI: 10.1177/08971900211015052
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intravenous Vitamin C in Critically Ill Patients With COVID-19 Infection

Abstract: Introduction The pathophysiology for Coronavirus Disease 2019 (COVID-19) infection is characterized by cytokine oxidative stress and endothelial dysfunction. Intravenous (IV) vitamin C has been utilized as adjuvant therapy in critically ill patients with sepsis for its protective effects against reactive oxygen species and immunomodulatory effects. The primary objective of this study was to evaluate the effects of IV vitamin C in critically ill patients with COVID-19 infection. Methods Retrospective observatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…The duration of treatment varied from four to 18 days. There was a low risk of bias for seven studies [8,11,14,21,22,24,25], while the risk of bias for two studies was high [13,20], as shown in Supplementary Table 2.…”
Section: Vitamin C Supplementationmentioning
confidence: 95%
See 2 more Smart Citations
“…The duration of treatment varied from four to 18 days. There was a low risk of bias for seven studies [8,11,14,21,22,24,25], while the risk of bias for two studies was high [13,20], as shown in Supplementary Table 2.…”
Section: Vitamin C Supplementationmentioning
confidence: 95%
“…The mean age was 61.0 ± 15.02, and 57.4% were males. These studies were conducted in China [8,14,22], Iran [13], Pakistan [20], Saudi Arabia [24], Turkey [25], and United States [11,21]. The studies provided daily doses alone [11,13,14,20e22,24,25] or daily doses after a loading dose [8].…”
Section: Vitamin C Supplementationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other observational studies with hospitalized COVID-19 patients who received high-dose intravenous vitamin C (HDIVC) also reported improvements in oxygen support status, reduced mortality [27], and improvements in the inflammatory response [28,29], and immune and coagulation function [28]. Different results were found by , in which intravenous vitamin C did not decrease the incidence of mortality, vasopressor requirements, sequential organ failure assessment score (SOFA score) or ventilator settings [30].…”
Section: Studies Addressing Vitamin C Supplementation During Covid-19mentioning
confidence: 99%
“…Moreover, some studies show that adjunctive intravenous administration of vitamin C for the treatment of infection in critically ill COVID-19 patients was unable to reduce the rate of mortality, ventilator settings, the requirement of vasopressor, etc. [84]. Therefore although vitamin C is vital for lessening the inflammatory response and assists in boosting the immune system of the host, there is a lack of substance to support that utilization of vitamin C at a high dose can be successful in the prevention or management of COVID-19.…”
Section: Nutritional Supplementsmentioning
confidence: 99%